The relationship between teacher's interpersonal behaviour and students' motivation to learn science in secondary schools in Kuching / Nur Syaifa Sazali - Sazali, Nur Syaifa (2015)
Due to the plummeted result of the Science subject in SPM these recent years, this study is vital in providing details regarding teachers' roles in students' motivation in classroom. This study investigated the relationship between teachers' interpersonal behaviour and students' motivation to learn Science in secondary schools in Kuching. A sample of 389 students out of 29, 468 populations in the Kuching district was selected through the simple random sampling technique to serve as research respondents. It was found that teachers' interpersonal behaviour among secondary school teachers in Kuching was at a moderate level. According to the result, both Proximity and Influence dimensions were found to be determinant of students' motivation. Nevertheless, Proximity dimension which describe teachers' level of cooperation was reported higher compared to Influence dimension which portrayed teachers' dominant towards students. Students' motivation to learn Science was verified at a moderate level of which intrinsic motivation was reported as the highest. Moreover, no significant differences were identified between gender, age and school location of respondents with their motivation to learn Science. Finally, the main finding demonstrated a significant positive relationship between teachers' interpersonal behaviour and students' motivation to learn Science in secondary school in Kuching. Therefore, it is concluded that a moderate level of teachers' interpersonal behaviour contributed to a moderate level of students' motivation to learn Science. As to develop and sustain students' interaction and boost their motivation in learning Science, teachers are recommended to find appropriate interpersonal behaviour pertain to the students' interest.